Determinants of intention to use an online bill payment system among MBA students - Ramayah, T.; Chin, Yee Ling; Mohd Suki, Norazah; Ibrahim, Amlus (UUM College of Business, 2008)
This study investigates and examines the intention to use an online bill payment among part time MBA students in Universiti Sains Malaysia (USM), Penang.A research framework based on the extended Technology Acceptance Model (TAM2) and Social Cognitive Theory is developed and modified in order to identify factors that would determine and influence the intention to use an online bill payment system.A survey involving a total of 120 university part time MBA students was conducted.The results reveal that perceived ease of use and perceived usefulness are the significant drivers of intention to use the online bill payment system.Subjective norm, image, result demonstrability and perceived ease of use were also found to be the key determinants of perceived usefulness whereas perceived risk was found to be negatively related to usefulness.This is very important as many researchers have shown that perceived usefulness is the most crucial factor in the decision to adopt and continue using a given technology.Computer self-efficacy plays a significant role in influencing the perceived ease of use of the online bill payment system.